Indonesian Pharmacy Students' Motivations for Learning English: A Qualitative Case Study - Noprival, Noprival (LPPM Universitas PGRI Silampari Lubuklinggau, 2022)
Despite the existence of studies on the motivation of learning, little scholarly work reports the motives of pharmacy students learning English. Further, a majority of those previous studies have been conducted using exclusively quantitative methods. To fill these empirical and methodological gaps, the current research used a qualitative descriptive case study method to explore the Indonesian pharmacy students' motivation for learning English. This study utilised in-depth interviews to gather information from participants. The thematic analysis of the semi-structured interviews presented that the students’ motivation for learning English were for academic purposes, cultural purposes, professional purposes, global interactions, and pleasure. The findings revealed that the orientations of learning English reported by the interviewees covered both integrative and instrumental motivation categories. Additionally, the results in this study contribute to our understanding of Indonesian pharmacy students’ motivation for learning English that can be practically used as references by students, lecturers, and curriculum designers.